Intangible Capital and Labour Productivity Growth: A Review of the Literature - Felix Roth (University of Hamburg, Chair of International Economics, 2019)
This paper surveys a wide range of studies on the impact of capital investment in intangible assets on labour productivity growth and highlights their main findings on. Surveying the literature at the country, industry and firm level, this paper finds evidence of the increasing importance of business investment in intangible assets in explaining the dynamics of labour productivity growth. Moreover, the findings reported in the literature surveyed suggest that in order to fully reap the benefits of investment in information and communication technology (ICT) and artificial intelligence (AI), it is essential for businesses to make complementary investment in intangible assets. In addition, the literature on the drivers of business capital investment in intangibles highlights the importance of having in place a well-endowed infrastructure of public intangibles. Judging from the wide range of economic literature surveyed, this paper finds that the contemporary economic debate now broadly acknowledges the importance of intangibles for the transformation of developed economies towards becoming fully-fledged knowledge economies.
Keywords: 330; Intangible Capital; Labour Productivity Growth; Total Factor Productivity Growth; Information and Communication Technology; Artificial Intelligence; European Union